The Influence of Service Quality, Price, Corporate Image, and Location Towards Customer Satisfaction on Autocare Universitas Muhammadiyah Yogyakarta - Dwi Kurniawati Amini; Dimas Bagus Wiranatakusuma (Universitas Muhammadiyah Yogyakarta, 2020)
This study aims to analyze the Influence of Service Quality, Price, Corporate Image, and Location towards Customer Satisfaction on Autocare Universitas Muhammadiyah Yogyakarta. This study uses a quantitative approach. The data used is primary data obtained by distributing questionnaires to the customers of Autocare UMY to 99 respondents. The method of sample collection uses a purposive sampling technique. The technique of data analysis that used in this study to process the data is multiple linear regression. The results of this study indicates that all independent variables namely Service Quality, Price, Corporate Image, and Location has a positive and significant influence on the dependent variable, namely Customer Satisfaction both simultaneously and partially.